2018
DOI: 10.12659/msm.905160
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive Changes in Bilateral Knee Joints Following Unilateral Anterior Cruciate Ligament Injury in Cynomolgus Monkeys

Abstract: BackgroundThe anterior cruciate ligament (ACL) is one of the most important structures maintaining stability of knee joints, and the proprioception of the ACL plays a key role in it. If the ACL is injured in the unilateral knee joint, it changes nerve electrophysiology, morphology, and quantity of the proprioceptors in the bilateral ACL. The aim of this study was to explore the proprioceptive changes in the bilateral knee joints following unilateral ACL injury, and to provide a theoretical foundation and ideas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…After the knee joint is damaged, the bilateral proprioception receptor's afferent information is asymmetrical (12), and thus precise control of the effector is lost. The middle pivot movement system adjusts the control procedure to compensate for the asymmetrical abnormal movement mode, and, consequently, the sensory information from the healthy side of the lower limb is reduced excessively to stabilize patient movement (13). In addition, if the affected limbs remain motionless, this reduced activity may cause decline and degeneration of muscle strength and muscle tension, therefore resulting in insufficient postural stability and increased probability of secondary injury, while post-injury pain might contribute to the poor balance performance (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…After the knee joint is damaged, the bilateral proprioception receptor's afferent information is asymmetrical (12), and thus precise control of the effector is lost. The middle pivot movement system adjusts the control procedure to compensate for the asymmetrical abnormal movement mode, and, consequently, the sensory information from the healthy side of the lower limb is reduced excessively to stabilize patient movement (13). In addition, if the affected limbs remain motionless, this reduced activity may cause decline and degeneration of muscle strength and muscle tension, therefore resulting in insufficient postural stability and increased probability of secondary injury, while post-injury pain might contribute to the poor balance performance (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…While these data seem to suggest that our sample of ACLR subjects did not possess somatosensory deficits, it is important to note that bilateral deficits in somatosensory function have been reported following ACLR. Similarly, bilateral declines in afferent neuron function have been reported following ACL injury in animal models . Though we are unable to determine if bilateral somatosensory deficits were present in our subjects without comparison with a healthy control cohort, it is clear from our findings that individuals with poorer somatosensory function in the ACLR limb display a gait biomechanics profile that is consistent with heightened PTOA risk.…”
Section: Discussionmentioning
confidence: 52%
“…Similarly, bilateral declines in afferent neuron function have been reported following ACL injury in animal models. 34 Though we are unable to determine if bilateral somatosensory deficits were present in our subjects without comparison with a healthy control cohort, it is clear from our findings that individuals with poorer somatosensory function in the ACLR limb display a gait biomechanics profile that is consistent with heightened PTOA risk.…”
Section: Discussionmentioning
confidence: 73%
“…Some studies reported a reduction in proprioception and instability in lower limb joints after an ACL injury. In this regard, Zhang et al reported that ACL injury reduced the number of proprioception receptors in monkeys, and ultimately, decreased proprioception in them [13]. Moreover, Relph et al reviewed the studies on reduced proprioception after an ACL injury [14].…”
Section: Resultsmentioning
confidence: 99%